2017
DOI: 10.1016/j.lwt.2016.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Use of fermented quinoa flour for pasta making and evaluation of the technological and nutritional features

Abstract: Pasta was prepared by replacing 20% of semolina with native and fermented quinoa flour and the effects of substitution on the technological and nutritional characteristics were evaluated. The addition of quinoa reflected the chemical composition of pasta, which had higher fiber, protein, and free amino acids content than semolina pasta, particularly in the case of pasta containing quinoa flour fermented with selected lactic acid bacteria. Furthermore, free amino acids, total phenols, and the antioxidant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 28 publications
(43 reference statements)
8
83
0
5
Order By: Relevance
“…The carbohydrate and moisture content has decreased ( P < 0.05), whereas the levels of protein, lipid and ash have increased ( P < 0.05) with increasing levels of SFP. A similar trend of an increase in protein, lipid, and ash contents has been reported for pasta made with shrimp meat (Kadam & Prabhasankar, ), green mussel (Vijaykrishnaraj et al ., ), tilapia ( Oreochromis niloticus ) flour (Monteiro et al ., ), broad bean (Giménez et al ., ), quinoa flour (Lorusso et al ., ) and legume flour (Bouasla et al ., ). The decrease in the moisture content may be able to be attributed to a change in the protein–starch interaction when compared to control pasta; the interaction between the different and increased proteins and the starch may have resulted into the entrapment of water molecules through electrostatic forces, and subsequently the more homogenous network developed with less free water (Zhang et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The carbohydrate and moisture content has decreased ( P < 0.05), whereas the levels of protein, lipid and ash have increased ( P < 0.05) with increasing levels of SFP. A similar trend of an increase in protein, lipid, and ash contents has been reported for pasta made with shrimp meat (Kadam & Prabhasankar, ), green mussel (Vijaykrishnaraj et al ., ), tilapia ( Oreochromis niloticus ) flour (Monteiro et al ., ), broad bean (Giménez et al ., ), quinoa flour (Lorusso et al ., ) and legume flour (Bouasla et al ., ). The decrease in the moisture content may be able to be attributed to a change in the protein–starch interaction when compared to control pasta; the interaction between the different and increased proteins and the starch may have resulted into the entrapment of water molecules through electrostatic forces, and subsequently the more homogenous network developed with less free water (Zhang et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…(), and Lorusso et al . () have all reported that the quality and content of protein used in pasta processing, as well as protein interactions in the continuous network, are important in the formation of carbohydrate – protein networks to obtain pasta of good cooking quality. The cooking loss of the control pasta was found to be 4.28 g/100 g. Cooking losses increased ( P < 0.05) with increasing levels of SFP ranging from 5.37 to 8.02 g/100 g. However, all pasta samples presented cooking losses below the technological acceptable limit 8 g/100 g. For good‐quality pasta, the residue should not exceed 8% of the dry weight of the pasta (Smatanová & Lacko‐Bartošová, ) and values obtained were within the limits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the pasta industry, pseudocereals and durum wheat blends are still a challenge since the addition of alternative ingredients markedly affects technological and sensory properties (Rizzello and others ). Recently, Lorusso and others () revealed that the substitution of 20% of semolina with quinoa flour improved the nutritional aspect of pasta, including free amino acids, total phenols, and the antioxidant activity of pasta; while the resulting pasta tenacity increased. Despite the great nutritional input, more work is required on the balance between substitution level and quality requirement.…”
Section: Ancient Grains‐based Foodstuffs: Nutritional Added Value Andmentioning
confidence: 99%
“…This replacement lead to an increase in availability of gluten-free products, and a decrease in the demand of durum wheat flour, which production is very limited leading to a partial or complete replacement of semolina with common wheat flours or other flours (Mastromatteo et al, 2011;Kim et al, 2016;Biernacka et al, 2017). However, the replacement of semolina is still a challenge, since the addition of other ingredients affects pasta properties (Lorusso et al, 2017). Shiitake (Lentinula edobes) mushrooms are the second most produced mushrooms in the world (about 25%) (Jiang et al, 2015 , 2003).…”
Section: Introductionmentioning
confidence: 99%